2013
DOI: 10.3109/19401736.2013.815168
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial 16S rRNA gene-based evolutionary divergence and molecular phylogeny ofBariliusspp.

Abstract: Barilius is an important genus of fish family Cyprinidae, which comprises 22 species from Indian region. This study aimed to characterize five commonly occurring Bariline species, for example, Barilius bakeri. Barilius gatensis. Barilius vagra. Barilius bendelisis and Barilius tileo, across the country using partial mitochondrial 16 S rRNA gene, to estimate the order of inter- and intra-species divergence among these species and to establish phylogenetic and evolutionary relationships. The average inter-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…The results of this study underscore the effectiveness of partial 16S mitochondrial gene sequences in elucidating phylogenetic relationships and genetic diversity among the Labridae species. These findings align with previous molecular studies, which have also demonstrated the utility of 16S rDNA as a barcoding system for revealing genetic variation among fish species and validating its suitability for resolving genetic relationships within this fish family (Craig et al, 2001;Pondella et al, 2003;Mitani et al, 2009;Quraishia et al, 2015;Singh et al, 2015;Saad, 2019;Wang, et al, 2023 ;Baldwin et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study underscore the effectiveness of partial 16S mitochondrial gene sequences in elucidating phylogenetic relationships and genetic diversity among the Labridae species. These findings align with previous molecular studies, which have also demonstrated the utility of 16S rDNA as a barcoding system for revealing genetic variation among fish species and validating its suitability for resolving genetic relationships within this fish family (Craig et al, 2001;Pondella et al, 2003;Mitani et al, 2009;Quraishia et al, 2015;Singh et al, 2015;Saad, 2019;Wang, et al, 2023 ;Baldwin et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…Similar type of interspecies polymorphism showed in Barilius spp. (Singh et al 2015) when 16S rRNA gene was compared among Barilius bakeri, B. gatensis, B. vagra, B. bendelisis and B. tile. Phylogenetic analysis: As Bombay duck is a lizardfish, a comparative study was performed among lizardfish from Harpadontidae and synodontidae family using the neighbor joining method, with bootstrap value 1000 where Labeo rohita was used as an out group. In the present study, Harpadon nehereus and H. microchir, belong to the family Harpadontidae, form a monophyletic clade with bootstrap value 96 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hal ini disebabkan karena gen mitokondria bersifat maternal sehingga pewarisannya tidak ditemukan adanya rekombinasi seperti halnya gen inti (Hartwell et al, 2015). Gen mitokondria 16S rRNA merupakan gen penanda yang penting dalam karakterisasi dan identifikasi genetik spesies serta untuk mengamati hubungan filogenetik inter spesies (Li et al, 2008;Singh et al, 2013). Adapun penggunaan gen mitokondria 16S rRNA untuk karakterisasi dan identifikasi spesies telah banyak digunakan pada ikan antara lain pada ikan belut (Arisuryanti et al, 2016), ikan Piscirickettsia salmonis dari Chili Selatan (Contreras-Lynch et al, 2015), dan ikan gabus (Firlianty et al, 2014).…”
Section: Pendahuluanunclassified